2008
DOI: 10.1093/molehr/gam086
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin H synthase-2 gene regulation in the amnion at labour: histone acetylation and nuclear factor kappa B binding to the promoter in vivo

Abstract: Increased prostaglandin H synthase-2 (PGHS-2) expression in the amnion is critical for the production of prostaglandins that induce labour. The aim of the present investigation was to determine whether PGHS-2 gene activity is controlled by NFkappaB transcription factors in term amnion in vivo as suggested by in vitro findings. Amnion membranes were collected after elective Caesarean section (n = 14) or spontaneous labour (n = 12) at term, and histone acetylation and transcription factor binding to the PGHS-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Increased acetylation at hypermethylated transcription start sites which lead to long term reactivation of anti-proliferative genes may be beneficial in the treatment of tumours when this information is known. This mechanism would be in addition to the reported synergistic apoptotic effect of methyltransferase and histone deacetylase inhibitors [28], [38].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increased acetylation at hypermethylated transcription start sites which lead to long term reactivation of anti-proliferative genes may be beneficial in the treatment of tumours when this information is known. This mechanism would be in addition to the reported synergistic apoptotic effect of methyltransferase and histone deacetylase inhibitors [28], [38].…”
Section: Discussionmentioning
confidence: 89%
“…Sonication was performed using 8×30-second cycles at 60% duty cycle in an ice bath and samples were further cooled for 30 seconds in between sonication cycles. Chromatin Immunoprecipitation was performed as previously described [28] with slight modifications. Antibodies were obtained from Upstate (Catalog numbers; α-H3Ac 06-599, α-H3K4me3 07-473, α-H3K9me3 17-625, α-H3K27me3 17-622) with the exception of the Rabbit IgG non-specific antibody from Santa Cruz Biotechnology (Catalog number SC2027).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, using ELISA-based DNA binding assays, Lappas and Rice have reported that term labor was associated with increased p65 activity in the amnion (but not the choriodecidua) following term labor [27]. In addition, using chromatin immunoprecipitation (ChIP), Mitchell et al found that p65 binding to the NF-κB responsive IκBα gene promoter (but not the cyclooxygenase-2 promoter) increased in the amnion following term labor [31]. In contrast with these prior reports, we were unable to document biochemical evidence of increased p65 binding activity in either the amniotic or the choriodecidual tissues following term labor.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these effects are mediated by the key inflammatory transcription factor NF‐κB . NF‐κB controls the genes that code for cytokines, chemokines, and enzymes that in turn synthesise prostaglandins . Silva et al.…”
Section: The Pro‐inflammatory and Anti‐inflammatory Roles Of The Decimentioning
confidence: 99%